Auto recalls and software quality in the automotive sector - Pancik, J.; Vemola, A.; Kledus, R.; Semela, M.; Bradac, A. (EAI Endorsed Transactions on Scalable Information Systems, 2018)
Software for automobiles is one from innovative factors in the automotive industry. Automobile is represented as an amount of embedded systems (embedded systems) and it is a very complex computing system. It is currently estimated that the average car has built-in software in the range of 100 million lines and in 2020 is already expected 300 million lines of code. The contribution is devoted to the management of safety and reliability of the software development for embedded systems designed for electromechanical (mechatronic) systems through quality assurance of embedded software. The contribution defines the term software quality assurance strategy, explains the role of standards such as ISO 26262 (Road vehicles - Functional safety), ISO 15504 (Automotive SPICE 3.0)
Keywords: software quality; auto recalls; automotive sector